Wnts in adult brain: from synaptic plasticity to cognitive deficiencies - Oliva, Carolina A.; Vargas, Jessica Y.; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2013)
During development of the central nervous system the Wnt signaling pathway has been implicated in a wide spectrum of physiological processes, including neuronal connectivity and synapse formation. Despite Wnt proteins and components of the Wnt pathway are expressed in the brain since early development to the adult life, little is known about its role in mature synapses. Here, we review evidences indicating that Wnt proteins participate in the remodeling of pre- and postsynaptic regions, thus modulating synaptic function. We include the most recent data in the literature showing that Wnts are constantly released in the brain to maintain the basal neural activity. Also, we review the evidences that involve components of the Wnt pathway in the development of neurological and mental disorders, including a special emphasis on in vivo studies that relate behavioral abnormalities to deficiencies in Wnt signaling. Finally, we include the evidences that support a neuroprotective role of Wnt proteins in Alzheimer’s disease. We postulate that deregulation in Wnt signaling might have a fundamental role in the origin of neurological diseases, by altering the synaptic function at stages where the phenotype in not yet established but when the cognitive decline starts.